До проблеми прочитання грекомовного покаянного графіті на фресці з образом св. Міни у Софії Київській - Корнієнко, В. (Спеціальні історичні дисципліни: питання теорії та методики, 2019)
Стаття присвячена висвітленню результатів сучасного дослідження грекомовного напису-графіті на фресці з образом св. Міни у північній внутрішній галереї Софійського собору. Аналізуються різночитання з опублікованими раніше прочитаннями напису російськими дослідниками Александрою Євдокимовою та Андрієм Виноградовим. The article covers the results of the modern research on the Greek graffiti inscription on St. Minа’s fresco in the northern inner gallery of St. Sophia Cathedral. The inscription was discovered by A. Evdokimova and included in its corpus publication of Greek inscriptions on the first floor of the St. Sophia Cathedral in Kyiv at number 22. The author proposed two possible variants of the reconstruction of the full text of the inscription. The difference between the modern research results and interpretation of graffiti inscription published earlier by Russian researchers Alexandra Evdokimova and Andrii Vinogradov are аnalyzed.